THE INFLUENCE OF BRAND IMAGE AND PROMOTION ON ZIS PAYMENT DECISIONS THROUGH ECOMMERCE WITH CONSUMER TRUST AS A MEDIATING VARIABLE - Hasibuan, Januar Khaidir; Herawati, Aty (Universitas Nahdlatul Ulama Surabaya, 2025)
This study aims to analyze the influence of brand image and promotion on Zakat, Infaq, and Shadaqah (ZIS) payment decisions through e-commerce, with consumer trust as the mediating variable. Along with the rapid development of information technology and e-commerce, digital platforms have become an important channel for philanthropic transactions, including ZIS payments. In Indonesia, the National Amil Zakat Agency (Baznas) has utilized e-commerce platforms to make it easier for people to fulfill their zakat obligations. However, there was a significant decrease in the number of ZIS payments in 2023, which prompted the need gacor777 for this study. This study uses a type of quantitative research with convenience sampling techniques. The sample consisted of 150 respondents who made ZIS payments through e-commerce, and the data was collected through questionnaires distributed using Google Forms. Data analysis was carried out using the SEM-PLS technique through SmartPLS software. The results show that brand image has a positive and significant influence on consumer confidence (p-value = 0.000) and ZIS payment decisions (p-value = 0.027). Promotions, on the other hand, did not show a significant influence on consumer confidence (p-value = 0.190) nor payment decisions (p-value = 0.243). Consumer confidence was proven to have a significant positive influence on ZIS payment decisions (p-value = 0.000). This study concludes that brand image plays an important role in increasing consumer trust and influencing ZIS payment decisions through e-commerce. While promotions did not show a significant impact in this context, the results provided insight into the importance of strengthening brand image to increase consumer trust and participation. Baznas needs to focus on strengthening its brand image and evaluating promotional strategies to address the decline in ZIS payments and improve the effectiveness of fundraising campaigns.